Analysis of Stability and Accuracy of Gas Flow in High Flow Nasal Canule for COVID-19 Patients - Muhammad Ridha Mak'ruf; Novella Lasdrei Anna Leediman; Andjar Pudji; Erwin L. Rimban (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
In December 2019, the world was introduced to a new coronavirus, severe acute respiratory syndrome (COVID-19).The primary strategy for COVID-19 patients is supportive care, using high-flow nasal oxygen therapy (HFNC) reported to be effective in improving oxygenation. Stability is the ability of a medical device to maintain its performance [1]. Medical equipment must have the stability necessary to maintain critical performance conditions over a period of time. Accuracy is the closeness of agreement between the value of a measuring quantity, and the value of the actual quantity of the measuring quantity[2].The purpose of this study is to ensure that the readings of the HFNC device are accurate and stable so that it is safe and comfortable when used on patients. The development of the equipment that will be used by the author adds graphs to the TFT LCD to help monitor stable data in real time so that officers can monitor the flow and fraction of oxygen in the device to be stable. This study uses Arduino Nano while the sensor used is the GFS131 sensor, then the results are displayed on the Nextion TFT LCD. The test is carried out with comparing the setting value of the HFNC tool that appears on the TFT LCD with a gas flow analyzer with a measurement range of 20 LPM to 60 LPM 5 times at each point. Based on measurements on the gas flow analyzer, the HFNC module has an average error (error (%)) of6.40%. Average uncertainty (Ua) 0.05. Conclusion from these results that the calibrator module has a relative error (error value) that is still within the allowable tolerance limit, which is ±10%, the tool is precise because of the small uncertainty and good stability of the stability test carried out within a certain time.